Pemanfaatan Platform Website E-Commerce Dalam Membangun Brand Awareness Oto 12 Drink - Sarah Mujahidah; Karissa Mulia; Sularno Sularno (CV. ITTC INDONESIA, 2025)
This paper discusses the use of e-commerce website platforms in building brand awareness for Oto 12 Drink, a micro, small, and medium enterprise located in Padang City. The purpose of this study is to determine the extent to which the use of e-commerce websites can increase brand awareness among consumers. The approach used is a descriptive qualitative approach with data collection methods in the form of observation, interviews, and documentation. The results of the study show that e-commerce websites play an important role in introducing products, providing clear information, and attracting consumer interest through interactive display designs and features. In addition, the integration of websites with social media also helps to expand the scope of promotion. Overall, the use of e-commerce websites has proven to be effective in building and strengthening brand awareness of Oto 12 Drink in today's digital age.